Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - Barbetti, M.; Banga, S.; Fu, T.; Li, Y.; Singh, D.; Liu, S.; Ge, Cynthia; Banga, S. (Springer Netherlands, 2014)
Twenty Brassica breeding populations derived from mass selection or inter-specific hybridization were field screened for resistance to three separate isolates of Sclerotinia sclerotiorum, the cause of Sclerotinia stem rot (SSR). Variation due to S. sclerotiorum isolates (P ≤ 0.001) and host populations (P ≤ 0.001) were highly significant. Populations × isolate interactions were also significant. S. sclerotiorum isolates, MBRS1 and MBRS5 were the most pathogenic and almost similar in terms of population reactions, with WW3 clearly being distinct and having a much smaller range in lesion length across the populations. There were wide ranging and variable responses in terms of resistance against S. sclerotiorum in Brassica napus and B. juncea, with or without B. carinata introgression, among these breeding populations. In B napus, ZY006 (resistant check) and Line6 (HZAU) were the most resistant, closely followed by Line1 (HZAU), OCRI-3 and Line5 (HZAU). Line6 (HZAU) showed excellent resistance against the highly virulent isolates MBRS1 and MBRS5; while OCRI-1 appeared most resistant against isolate WW3. The B. juncea × B. carinata hybrid JC134 (PAU) was the most resistant against isolate MBRS5 and B. juncea RH9902 × JN026 the most resistant against isolate MBRS1. B. napus lines Line2 (HZAU), Line4 (HZAU), OCRI-3; and OCRI-4, and the B. napus × B. carinata hybrid Surpass4000 NCB4 (PAU), showed a significant degree of isolate-dependency in their reactions.In contrast, some other genotypes such as B. napus lines Line1 (HZAU), OCRI-5; Ding 110× Oscar and, particularly, Line5 (HZAU), were largely isolate-independent, making them ideal sources of resistance to target and exploit in developing new commercial cultivars with more effective resistance to SSR across multiple pathotypes of this pathogen. Cluster analysis allowed categorization of the test populations into five groups, based on their resistant responses. B. napus ZY006 was the sole genotype in the most resistant group. B. napus lines Line6 (HZAU), Ding 110 × Oscar (HAU) and Line4 (HZAU) clustered in another genetically distinct resistant group. That lines could be grouped into those with similar responses across the three different isolates of S. sclerotiorum will save breeders much time and expense by eliminating duplication of breeding efforts that occurs from using genotypes that are essentially similar in terms of host resistance against this serious pathogen. Further, that populations of similar levels of resistance but narrow variation in the resistance range could be identified is significant, as these are most likely to reliably provide breeders with advanced populations that not only consistently display the level of resistance expected but also reflect genetic diversity of resistance sources needed to successfully develop new more-resistant commercial varieties.